Antagonistic and plant growth promoting activity of Trichoderma spp. against soil borne diseases of chickpea - Nagamani, P; Bhagat, Someshwar; Biswas, M K; Viswanath, K (Indian Journal of Plant Protection, 2020)
Among twenty Trichoderma isolates, KNN 4 showed maximum inhibition of mycelia growth by 81.1% against R.bataticola, KNPG 3 showed against S. rolfsii (80.7%) and ATPU 1 inhibited the mycelia growth of Fusarium oxysporum f. sp. ciceri. (84.1%). Chickpea seeds were primed with twenty isolates of Trichoderma using both mycelia and conidial inocula, to assess their effectiveness in improving seed germination, vigour index and seedling biomass of the crop. Signifcant enhancement in the seed germination (%), vigour index and seedling biomass were noted. Among the two forms of inocula, the mycelial form gave better responses with respect to enhanced seed germination percentage and increasing seed vigour index either in terms of calculated vigour index or estimated biomass on dry weight basis in two conditions. In pot culture studies, highest per cent germination of seed was obtained (96.67%) for the isolate ATPU 1 and highest vigour index was recorded in KN0 9 (3627.7) when crop seed was primed with mycelia form of inoculum. Highest vigour index was recorded in ATPU 1 (2063.0) and lowest vigour index (1327.0) for the isolate KJ 12 was recorded in mycelia form of inoculum under in vitro studies.